Leishmania Parasites Differently Regulate Antioxidant Genes in Macrophages Derived From Resistant and Susceptible Mice - Bichiou, Haifa; Rabhi, Sameh; Ben Hamda, Cherif; Bouabid, Cyrine; Belghith, Meriam; Piquemal, David; Trentin, Bernadette; Rabhi, Imen; Guizani-Tabbane, Lamia (Frontiers in Cellular and Infection Microbiology, 2021)
Macrophage-Leishmania interactions are central to parasite growth and disease outcome. Macrophages have developed various strategies to fight invaders including oxidative burst. While some microorganisms seem to survive and even thrive in an oxidative environment others are susceptible and get killed. To counter oxidative stress, macrophages switch cytoprotective and detoxifying enzymes expression which are downstream targets of the Nuclear factor E2-related factor 2 (Nrf2), to enhance cell survival. We have explored the transcription of NRF2 and of its target genes and compared the effect of the parasite on their transcription in Bone Marrow derived Macrophages (BMdMs) from Leishmania resistant and susceptible mice. While heme oxygenase 1 (HO-1) transcription is independent of genetic background, transcription of glutathione reductase (Gsr) and of cysteine/glutamate exchange transporter (Slc7a11), involved in glutathione accumulation, is differentially regulated in BMdMs derived from both mouse strains. We also show that except for HO-1, known to favour the survival of the parasite, the transcription of the selected genes including Gsr, CD36 and catalase (CAT) is actively repressed if not at all time points at least at the later ones, by the parasite specially in Balb/c BMdMs. Consistent with these results, we found that the silencing of NRF2 in our hands, increases the survival and multiplication of the parasite.